Ventilation of the giant nests of Atta leaf-cutting ants: does underground circulating air enter the fungus chambers? - Bollazzi, M.; Forti, L. C.; Roces, F. (Springer Basel Ag, 2012)
Nest ventilation should be particularly relevant for the huge colonies of leaf-cutting ants, genus Atta. Considerable amounts of O-2 are consumed and CO2 produced by both the fungus gardens and the ants inside nest chambers, which are located at deep soil layers characterized by high CO2 and low O-2 concentrations. In this work, passive nest ventilation was investigated in field Atta capiguara and Atta laevigata nests, first, by evaluating air movements through the nest using propane as tracer gas as well as the CO2 and O-2 concentrations of the circulating air, and second, by exposing the internal nest morphology with the use of cement casts and excavations. Results showed that even though outflow of CO2-rich air and inflow of O-2-rich air occurred at high-placed and low-placed openings, respectively, supporting a wind-induced interpretation of air movements through the nest, circulating air was never detected inside fungus chambers. The CO2 and O-2 levels inside the fungus chambers increased and decreased with increasing soil depth, respectively, and were in the range observed in the soil phase. Based on the underground nest architecture, it is concluded that although the external shape of the nest induces underground air circulation, the inflowing air is unable to directly reach the fungus chambers. It is argued that colony respiration completely depends on diffusive flows between the chamber air and the adjacent nest and soil atmospheres. Circulating air, although not directly renewing the air inside the nest chambers, may contribute to colony respiration by increasing the capacity of the nest and soil airs to act as an O-2-source and a CO2-sink, because of the decrease in the CO2 and the increase in the O-2 levels in the underground air phase. Possible adaptations of both ants and fungus to the high CO2 and low O-2 concentrations usually found in soils are discussed.
Keywords: Ants; Atta; Nest; Ventilation; Respiration; Diffusion